Surgical-site mucormycosis infection in a solid-organ transplant recipient and a concise review of the literature. Issue 12 (10th December 2019) - Haque, Husham; Nettboy, Scott; Kumar, Sunil
Abstract : Surgical-site mucormycosis infections in solid-organ transplant recipients are rare conditions, with only 15 previously reported cases. We describe a case of a 49-year-old man who received a liver transplant due to alcoholic cirrhosis. On postoperative day 14, necrosis was noticed at the surgical site. After mucormycosis was diagnosed, monotherapy with amphotericin was started along with surgical debridements. Due to continued clinical deterioration, triple antifungal therapy was started with amphotericin, micafungin and posaconazole. Treatment with a granulocyte-macrophage colony-stimulating factor was also started. Despite therapy, the patient expired on postoperative day 31. We review the risk factors for mucormycosis infection in solid-organ transplant recipients as well as evidence for current treatment options. We also review the 15 previously reported cases of surgical-site mucormycosis infections in solid-organ transplant recipients, including time to infection, infecting organisms, mortality and treatments.